HIDROTERAPI RENDAM HANGAT SEBAGAI UPAYA PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Nanda Ayu Paramita; Nur Melizza (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Hypertension is a chronic disease that can cause various serious complications and requires appropriate treatment. In addition to pharmacological therapy, non-pharmacological interventions such as warm immersion hydrotherapy can be used to help lower blood pressure. Objective: This study aimed to determine the effectiveness of warm immersion hydrotherapy on lowering blood pressure in hypertensive patients. Method: The method used was a quasi-experimental study with a pretest–posttest design without a control group. The intervention was carried out by soaking the feet or lower body in warm water for 15–20 minutes. Blood pressure was measured before and after the intervention. Result: The results showed a decrease in systolic and diastolic blood pressure after warm immersion hydrotherapy. Conclusion: It can be concluded that warm immersion hydrotherapy is effective as a complementary therapy in helping to lower blood pressure in hypertensive patients.